2017
DOI: 10.22452/mjcs.vol30no3.5
|View full text |Cite
|
Sign up to set email alerts
|

Pairwise Test Data Generation Based On Flower Pollination Algorithm

Abstract: Owing to an exponential increase in computational time associated with increasing number of system components, exhaustive testing is increasingly become impractical. Here, many researchers opt to adopt pairwise testing to minimize the overall number of tests. Recently, many existing works are focusing on the use of Search-Based algorithms as the basis of the implementation algorithm for pairwise test suite generation; however, there is no single strategy that can be the best for all cases. Currently, researche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…This approach uses the Levy Flight equation to generate population globally. However, based on the final result, it is found that this approach cannot outperform other approaches in some covering arrays with values 313 and 513822 [4].…”
Section: Related Workmentioning
confidence: 96%
“…This approach uses the Levy Flight equation to generate population globally. However, based on the final result, it is found that this approach cannot outperform other approaches in some covering arrays with values 313 and 513822 [4].…”
Section: Related Workmentioning
confidence: 96%
“…The first category uses a single meta-heuristic algorithm as the search engine for the test case. Example of this category includes SA [1], GA [1,2], ACA [2], PSO [3], HS [4], FPA [7], Whale Optimization Algorithm [47] and CS [5]. The second category uses adaptive or hybridization of meta-heuristics algorithms as the search engine.…”
Section: Related Workmentioning
confidence: 99%
“…In the field of software testing, many research adopts meta-heuristic algorithms as the basis of dealing with combinatorial explosion problem (e.g. Simulated Annealing (SA) [1], Genetic Algorithm (GA) [1,2], Ant Colony Algorithm (ACA) [2], Particle Swarm Optimization [3], Harmony Search (HS) [4], Cuckoo Search (CS) [5,6] and Flower Pollination Algorithm (FPA) [7]) related to t-way test suite generation. The t-way test suite generation (where t indicates the interaction strength), involves finding an optimized set of test cases that covers the t-way interaction strength.…”
Section: Introductionmentioning
confidence: 99%
“…RashmiRekhaSahoo et.al proposed a distance based fitness function for generating test inputs for path coverage. [11] Uses search based approach PSO with ICF function Abdullah B. Nasser et.al proposed a Flower Pollination Algorithm [12] which reduced the size of test data thereby saving time and effort. [13] Introduced a modified Bacterial Foraging Technique (BFT) for solving the economic load dispatch problem.…”
Section: Related Workmentioning
confidence: 99%